2024
DOI: 10.1038/s41420-023-01792-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac cell senescence: molecular mechanisms, key proteins and therapeutic targets

Yi Luan,
Xiaofan Zhu,
Yuxue Jiao
et al.

Abstract: Cardiac aging, particularly cardiac cell senescence, is a natural process that occurs as we age. Heart function gradually declines in old age, leading to continuous heart failure, even in people without a prior history of heart disease. To address this issue and improve cardiac cell function, it is crucial to investigate the molecular mechanisms underlying cardiac senescence. This review summarizes the main mechanisms and key proteins involved in cardiac cell senescence. This review further discusses the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 230 publications
0
1
0
Order By: Relevance
“…The protocol is expected to produce a relatively pure CM population 3 and observed metabolic changes dominated by the differentiation process in iPSC-CMs 46 rather than proliferation or senescence. [69][70][71] We found that ORI can detect increased oxidative activity during early maturation (decreased ORR over time) and separates cells by differentiation efficiency. Furthermore, we demonstrated the ability to perform extended culture and repeated ORI on synthetic hydrogels.…”
Section: Discussionmentioning
confidence: 76%
“…The protocol is expected to produce a relatively pure CM population 3 and observed metabolic changes dominated by the differentiation process in iPSC-CMs 46 rather than proliferation or senescence. [69][70][71] We found that ORI can detect increased oxidative activity during early maturation (decreased ORR over time) and separates cells by differentiation efficiency. Furthermore, we demonstrated the ability to perform extended culture and repeated ORI on synthetic hydrogels.…”
Section: Discussionmentioning
confidence: 76%